العلاقة بين الحس الفكاهي والصلابة النفسية لطفل ما قبل المدرسة - مصطفى، الزهراء مصطفى محمد (جامعة أسيوط - كلية التربية للطفولة المبكرة, 2021)
يهدف البحث إلى التعرف على العلاقة بين الحس الفكاهي وعلى الصلابة النفسية لطفل ما قبل المدرسة، مع الكشف عن الفروق فى الحس الفكاهي والصلابة النفسية تبعا لمتغير (الحالة الصحية -النوع). تم تطبيق البحث على مجموعة من الأطفال عددهم (٥٠) طفلا وطفلة فى مرحلة ما قبل المدرسة تتراوح أعمارهم بين (٦-٥) سنوات، واستخدم فى البحث استمارة المستوى الاقتصادى والاجتماعي (إعداد الباحثة)، اختبار المصفوفات المتتابعة لجون رافن، بطاقة ملاحظة الحس الفكاهى لطفل ما قبل المدرسة (إعداد الباحثة)، مقياس الصلابة النفسية لطفل ما قبل المدرسة (إعداد الباحثة). وأسفرت نتائج البحث عن الاتي: وجود علاقة بين الحس الفكاهي والصلابة النفسية لطفل ما قبل المدرسة، عدم وجود فروق بين درجات الأطفال على الدرجه الكلية لبطاقة الحس الفكاهي وفى البعد المعرفي تبعا لمتغير الحالة الصحية للأطفال،مع وجود فروق فى البعد الانفعالى لصالح الطفل السليم، عدم وجود فروق تبعا للحالة الصحية للأطفال فى الصلابة النفسية، عدم وجود فروق تبعا لمتغير النوع في الحس الفكاهي للأطفال، وجود فروق تبعا لمتغير النوع لصالح الإناث على الدرجه الكلية لمقياس الصلابة النفسية و بعد الالتزام، مع عدم وجود فروق تبعا لمتغير النوع على بعد التحكم، ووجود فروق تبعا لمتغير النوع لصالح الذكور على بعد التحدي .
The research aim to identify the relation between Sense Of Humor and psychological hardness for Pre-school child, with knowing the difference in Sense of Humor and psychological hardness for Pre-school child according to (health status — gender) The research applied on group of children sample consists of(50) children (males and females) from Pre-school stage between the age of 0-1 years, the research use form of economic & social level (prepared by the researcher), Sequential matrix test by jon rafen, observation card of Sense of Humor for Pre-school child (prepared by the researcher), scale of psychological hardness for Pre-school child (prepared by the researcher). Research results are that there is a relation between Sense of Humor and psychological hardness for Pre-school child, there is no difference between child grads at total grad for form of Sense of Humor and in cognitive scale according to health status for children, with differences in emotional scale for healthy child, No differences according to health status at psychological hardness, There is differences according to gender for female at total grad for scale of psychological hardness and in Commitment scale, No differences according to gender at Control scale, there is differences according to gender for male at Challenge scale.
Keywords: علم النفس -- الفكاهة الإيجابية -- الأساليب التربوية